The effects of different dry mixing methods and coating concentration to NMC-811 battery performance - Leo, Kelvin (Nanyang Technological University, 2022)
Due to the emerging environmental issues, lithium-ion batteries (LIBs) have become one of many alternatives that account for a large proportion of the current battery market and have wide applications in our daily lives. Among many variations of lithium-ion batteries, NMC-811 batteries (LiNi0.8Co0.1Mn0.1O2) are favourable due to their high performance yet low-cost materials. However, some issues emerge from this type of battery: microcracks, phase transformation, and side reactions between electrolytes and their surrounding environment. These issues decrease the overall battery performance.